The non-operative resin treatment of proximal caries lesions (2012)
Epidemiological data show that the prevalence of caries on proximal surfaces in need of operative treatment is very high around the world, both in the primary and the permanent dentition. This article presents two new treatment methods: proximal sealing and proximal infiltration. The indications are progressing proximal caries lesions, radiographically with a depth around the enamel-dentine junction. A small number of studies regarding the effect of sealing and infiltration on proximal caries versus the use of fluoride varnish, placebo treatment and flossing instructions have been carried out. About half of the studies disclose a not significant difference between test and control treatment. In the other half, the therapeutic effect is significant and corresponds to about 30% reduction in lesion progression. However, longitudinal studies of longer duration are lacking.